Discharge Disposition After Limb Amputation in a Publicly Funded Health Care System - Samuel Kwaku Essien PhD; Audrey Zucker-Levin PhD, MSPT (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
Understanding discharge disposition (DD) after limb amputation (LA) surgery allows health care providers and policy makers to adapt resources based on need. Studying independent prognostic factors for DD after LA in Canada eliminates the significant influence of payor source, as reported by researchers in the United States. We hypothesize disparities exist among DDs after LA in a publicly funded health care system. Retrospective review of Saskatchewan’s linked administrative health data from 2006 to 2019 was used to identify independent socio-demographic factors, amputation levels, amputation predisposing factors (APF), and surgical specialty on 5 DD’s: inpatient, continuing care, home with support services (H/W), home with no support services (H/WO), and those who died at the hospital after LA. We found age, amputation level, and APF play a significant role in determining discharge to all dispositions; gender was significantly associated with discharge to continuing care and H/WO; place of residence was associated with discharge to inpatient facilities, continuing care, and H/W; income was not associated with any DD other than H/W; surgical specialty was associated with discharge to all dispositions except death. The findings suggest that disparities in DD following LA exist even after eliminating the influence of payor source. Health care providers and policy makers should consider these findings in preparation for future needs.